Rancangan Strategi Media Sosial PT XYZ pada Tahun 2021 - Adinugroho, Antonius Denny; Hidayati, Aprihatiningrum (Research Center and Case Clearing House PPM School of Management, 2021)
PT XYZ is a low-cost airline or low-cost airline, which is actively engaged in developing the company's digital presence to increase transaction rates and assess relationships with relevant and trusted consumers. Recently, the aviation industry has faced tough challenges, especially the Covid-19 pandemic that has hit the world. Indonesian airline companies have long been active in building their digital presence to become market leaders, these airlines can use social media; Instagram, Facebook and Twitter. This research hopes to help PT XYZ increase its competitive advantage by analyzing the 3C method, namely Customer, Competitor, and Company analysis. The data obtained for the research is the result of survey data from apprenticeship reports, internet observations (netnography), and study report documents. With the data that has been obtained, a SWOT analysis is then carried out to find weaknesses, opportunities, and threats that the company could have. The results are then used to plan with the TOWS Matrix to produce several social media designs that can be implemented by PT XYZ. The resulting strategic design to increase corporate transactions are; (1) photo contest, (2) story contest, (3) open channels on Whatsapp social media (4) use Instagram Shops, and (5) collaborate with content creators on the Youtube platform. The strategic design undertaken is expected to increase consumer transactions in the B2C market.